2015
DOI: 10.1093/toxsci/kfv117
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and Functional Characterization and Assessment of iPSC-Derived Hepatocytes forIn VitroToxicity Testing

Abstract: Drug-induced liver injury (DILI) remains a great challenge and a major concern during late-stage drug development. Induced pluripotent stem cells (iPSC) represent an exciting alternative in vitro model system to explore the role of genetic diversity in DILI, especially when derived from patients who have experienced drug-induced hepatotoxicity. The development and validation of the iPSC-derived hepatocytes as an in vitro cell-based model of DILI is an essential first step in creating more predictive tools for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
57
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(61 citation statements)
references
References 77 publications
4
57
0
Order By: Relevance
“…Freshly isolated human hepatocytes are currently the gold standard cell type for transplantation as well as for cell modeling for drug discovery and development, and various toxicity tests (15,16,21,25,34). However, limited availability, short life span, loss of functionality upon isolation and culturing in vitro, dedifferentiation, and failing to represent the polymorphic population urge the development of alternative cell sources that do not have these drawbacks (15,25,31,34).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Freshly isolated human hepatocytes are currently the gold standard cell type for transplantation as well as for cell modeling for drug discovery and development, and various toxicity tests (15,16,21,25,34). However, limited availability, short life span, loss of functionality upon isolation and culturing in vitro, dedifferentiation, and failing to represent the polymorphic population urge the development of alternative cell sources that do not have these drawbacks (15,25,31,34).…”
mentioning
confidence: 99%
“…Moreover, human induced pluripotent stem cells (hiPSCs) generated from the transfection of somatic cells with pluripotency factors, may be employed in drug discovery as disease models (1,4,20,31). In addition, these cells can also be utilized for patient specific treatment (1,20).…”
mentioning
confidence: 99%
“…The other is the large varia- tions between lots due to their different genetic and environmental backgrounds. HiPSC-derived hepatocytes have been anticipated to be used in in vitro ADMET studies as alternatives to PHHs because researchers are able to obtain the hiPSC-derived hepatocytes from the same origin repeatedly (Holmgren et al, 2014;Lu et al, 2015;Sirenko et al, 2014). PHHs were often used as controls in the studies of hiPSC-derived hepatocytes.…”
Section: Discussionmentioning
confidence: 99%
“…This scenario suggests the feasibility of modeling the metabolic differences observed frequently in the human population. Recently, Lu et al (2015) demonstrated the ability of iPSCs-derived HLCs to reproduce key characteristic metabolic and adaptive responses can be attributed to the hepatotoxic effects of APAP and trovafloxacin in vivo (Lu et al 2015). Takayama et al (2012) used the transduction with an adenovirus encoding HNF4-α to promote hepatic maturation of both ESCs and iPSCs, and studied whether their HLCs could be used to predict metabolism-mediated toxicity (Takayama et al 2012).…”
Section: The Use Of Ipscs-derived Hlcs For Hepatotoxicity Assessmentmentioning
confidence: 99%